Maternal hyperglycemia during labor and related immediate post-partum maternal and perinatal outcomes at the Yaoundé Central Hospital, Cameroon - Djomhou, Manuella; Sobngwi, Eugene; Noubiap, Jean Jacques N.; Essouma, Mickael; Nana, Philip; Fomulu, Nelson J. (Journal of health, population and nutrition, 2016)
Data on the prevalence and complications of gestational diabetes are very scarce in Cameroon. The aim of this study was to evaluate the uptake of screening for gestational diabetes and assess the immediate post-partum outcome of hyperglycemic parturient mothers and perinatal outcome of their babies. A prospective cohort study was held at the Maternity of the Yaoundé Central Hospital from March to June 2013. One hundred volunteer women in labor without overt diabetes mellitus and having fasted for 8 to 12 h were recruited. No intervention was given. A clinical examination was done and capillary glucose recorded. Parturient women were categorized into two groups (hyperglycemic and non-hyperglycemic subjects) based on glycemia results interpreted according to the International Association of Diabetes and Pregnancy Study Groups. Mothers' clinical examination was repeated and neonates examined immediately after delivery. Perinatal outcomes associated with maternal hyperglycemia during labor were assessed using relative risks. A p value <0.05 was considered statistically significant. One hundred women with a mean age of 27 (SD 6) years were recruited. Of them, 22 (22 %) had already been screened for gestational diabetes at baseline. Thirty-one (31 %) were diagnosed with hyperglycemia during labor, and this condition was highly associated with macrosomia in neonates (RR = 8.9, 95 % CI 2.70-29.32; p < 0.001). Other complications associated with maternal hyperglycemia during labor were perineal tears, cesarean section, and intrauterine fetal death, though the association was not statistically significant. The main finding of this study is that maternal hyperglycemia during labor is highly associated with macrosomia in neonates. About a third of mothers were concerned with hyperglycemia during labor, and gestational diabetes was insufficiently screened in this series.